PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, ENTERPRISE RISK MANAGEMENT, DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI - Nauli, Cindy; Ridaryanto, Petrus (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2023)
The purpose of this research is to analyze the effect of CSR disclosure, enterprise risk management, and audit committee to firm value mediated by earnings management. CSR disclosure is measured by the level of firm’s disclosure of 45 aspect in 3 large component of CSR based on GRI standards. Enterprise risk management is measured by the disclosure of 20 component in 5 risk managemet dimensions conducted by COSO. Audit committee is measured by the number of audit committee with accounting or finance education background. The population of this research is non-financial industries listed in Indonesia Stock Exchange at the period of 2017-2019. Samples are taken using random sampling technique. The result of this research indicates that CSR disclosure, enterprise risk management, and audit committee have no significant influence towards earnings management. CSR disclosure and enterprise risk management also have no significant influence towards firm value, whereas audit committee has negative significant influence towards firm value. Earnings management also has no significant influence towards firm value